Hepatitis C virus-specific T cell receptor mRNA-engineered human T cells: impact of antigen specificity on functional properties - Balasiddaiah, Anangi; Lohmann, Volker (Journal of virology, 2017)
Therapy with genetically modified autologous T cells has shown great promise in cancer therapy. For an efficient control of hepatitis C virus (HCV) infection, cytotoxic T cells (CTL) are pivotal, but persistence of activated T cells may lead to liver toxicity. Here, anti-HCV T cell receptors (TCRs) recognizing the HCV nonstructural (NS) NS3 or NS5 viral peptide target were examined by mRNA transfection of human peripheral blood lymphocytes (PBLs) derived from healthy donors as well as chronically infected HCV patients. Immunological analysis shows that while the CTLs expressing the NS5-specific TCR reduced HCV RNA replication by a noncytotoxic mechanism, the NS3-specific TCR-redirected CTLs were polyfunctional and inhibited HCV RNA replication through antigen-specific cytotoxicity. Transcriptome signatures from these two types of CTL responses revealed uniquely expressed gene clusters upon encountering hepatoma target cells presenting endogenously expressed HCV proteins. The NS3 TCR induced a rapid expression of apoptotic signaling pathways and formation of embryonic gene clusters, whereas the NS5A TCR activation induced extended proliferative and metabolic pathways as the HCV target cells survived. Our results provide detailed insights into basic HCV T cell immunology and have clinical relevance for redirecting T cells to target virally infected hepatoma cells. IMPORTANCE Due to the protective ability of HCV-specific T cells and the hepatotoxic potential that they possess, there is a great need for the understanding of the functional aspects of HCV-specific T cells. To circumvent the low level of precursor frequency in patients, we engineered primary CD8+ T cells by mRNA TCR vectors to confer HCV specificity to new T cells. HCV TCRs that differ in antigen specificity and polyfunctionality were examined. mRNA TCR engineering of peripheral blood lymphocytes from healthy donors or chronically infected HCV patients resulted in strikingly high levels of HCV TCR expression and HCV-specific responses. While a cytotoxicity response from a polyfunctional T cell activation caused hepatotoxicity and the rapid induction of apoptotic signaling pathways, the noncytotoxic T cell activation showed extended proliferative, metabolic pathways and persistence of HCV target cells. Our results provide detailed insights into basic HCV T cell immunology and have clinical relevance for immune protection of HCV-associated diseases.